Evaluation of Electricity Generation and Wastewater Treatment from Palm Oil Mill Effluent Using Single and Dual Chamber Microbial Fuel Cell - Islam, M. Amirul; Chee, Wai Woon; Baranitharan, E.; Yousuf, Abu; Cheng, C. K.; Khan, Maksudur R. (Universiti Malaysia Pahang, 2016)
Microbial Fuel Cells (MFCs) can be simultaneously used for the treatment of wastewater and generation of electricity. In this study, single chamber air-cathode MFC (sMFC) and double chambered MFC (dMFC) were compared for the palm oil mill effluent (POME) treatment and generation of electricity while Pseudomonas aeruginosa (ATCC – 27,853) was used as inoculum and POME used as substrate. The dMFC was efficient and found to be producing maximum power density of 4.2 W/m3 whereas sMFC produced a maximum power density 1.7 W/m3. Moreover, the dMFC showed higher COD (54%) removal when compared with sMFC (41%). The significant power generation and COD removal efficiency observed in dMFC might be attributed to the microbial catalyzed and reversible electrochemical reactions occurring in the anodic chamber and cathode chamber of dMFC. These results suggest that dMFC is efficient than sMFC in producing electricity as well as in treating wastewater.